2002
DOI: 10.1074/jbc.m107979200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Not1p, a Component of the Ccr4-Not Complex, a Global Regulator of Transcription, and Dhh1p, a Putative RNA Helicase

Abstract: The Ccr4-Not complex is a global regulator of transcription that affects genes positively and negatively and is thought to regulate transcription factor IID function. Two components of this complex, Caf1p and Ccr4p, are directly involved in mRNA deadenylation, and Caf1p is associated with Dhh1p, a putative RNA helicase thought to be a component of the decapping complex. In this work, we tried to determine whether Dhh1p might interact with the Ccr4-Not complex. We found that, first, not mutations displayed seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 25 publications
3
82
0
Order By: Relevance
“…The RNA-helicase Dhh1 binds many Lsm domain proteins and forms part of complexes involved in mRNA decapping, deadenylation and subsequent decay. [34][35][36] In addition, the association of Pbp1 and Lsm12 suggests that the Lsm domains of both proteins may assemble as heteromers as it is known from many other Lsm domain proteins. 20 Taken the length of about 722 and 1312 amino acid residues, respectively, into account, Pbp1 and ATX2 may form part of large complexes and work as scaffolding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-helicase Dhh1 binds many Lsm domain proteins and forms part of complexes involved in mRNA decapping, deadenylation and subsequent decay. [34][35][36] In addition, the association of Pbp1 and Lsm12 suggests that the Lsm domains of both proteins may assemble as heteromers as it is known from many other Lsm domain proteins. 20 Taken the length of about 722 and 1312 amino acid residues, respectively, into account, Pbp1 and ATX2 may form part of large complexes and work as scaffolding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The map indicates that Pbp1 binds the DEAD/H-box RNAhelicase Dhh1 that plays a major role in mRNA turnover and degradation. [34][35][36] Furthermore, Pbp1 is clearly linked to the nuclear export machinery of mRNA 37 by the exportin Crm1 38 and the nucleoporin Nup145. 39 These findings match experimental results that observed Crm1 in complex with other nucleoporins and RanGTP.…”
Section: Analysis Of Pbp1 Functionsmentioning
confidence: 99%
“…Interestingly, DDX6 is a homologue of yeast Dhh1, which interacts with the Ccr4 -Not complex (Coller et al, 2001;Maillet and Collart, 2002). Moreover, like CNOT7 and CNOT8, DDX6 is a component of cytoplasmic P-bodies (Cougot et al, 2004), which are enriched in translationally repressed mRNA molecules and proteins participating in microRNA-mediated translational repression and mRNA decay (Garneau et al, 2007;Parker and Sheth, 2007).…”
Section: Cnot7 and Cnot8 Are Important For Efficient Cell Proliferatimentioning
confidence: 99%
“…Physical and genetic interactions was amplified by PCR from a HeLa cell cDNA expression library and cloned into a derivative of a yeast expression vector between Dhh1p and Ccr4p, Pop2p, and Not1p have (pG1;Schena et al 1991) containing two HA epitope sebeen reported (Hata et al 1998;Coller et al 2001; quences inserted at the BamHI site. CLN3 derivatives were Maillet and Collart 2002). Ccr4p is the catalytic subexpressed from the GAL1 promoter using the vector pYES2 unit in the yeast deadenylation machinery, and Pop2p (Clontech, Palo Alto, CA).…”
mentioning
confidence: 99%